Etiology of Borderline Intellectual Functioning - Kim, Hyo-Won (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2024)
Borderline intellectual functioning (BIF), characterized by intelligence quotient scores between 70 and 85, can lead to challenges in daily life. This review explored the multifaceted nature of BIF by examining the interplay between genetic predisposition, prenatal/perinatal factors, environmental influences, and underlying medical conditions.